Developing the Juramento into an Evidence-Based Brief Intervention: A Brief Report. (June 2021) - Garcia, Victor; Lambert, Emily; Heckert, Alex; Pinchi, Nahomy Hidalgo
Introduction: This brief report recommends how the effectiveness of the juramento, a practice found in Mexican Catholicism, can be enhanced by combining it with Screening, Brief Intervention, and Referral to Treatment. The juramento is a grassroots intervention around a sacred pledge made to Our Lady of Guadalupe to abstain from alcohol from 6 months to 1 year. Method: The recommendations are made possible from an ongoing qualitative study on the use of the juramento among Mexican immigrant farmworkers in southeastern Pennsylvania. The subsample for this report is 15 Mexican immigrant farmworkers who made a juramento and two priests who administer the intervention. Results: Adding the Alcohol Use Disorders Identification Test and a referral to treatment in the counseling session of the juramento keeps its religious and cultural appeal. The core of the intervention—the ritualized pledge to Our Lady of Guadalupe—remains intact. Conclusion: Approaching the juramento with an evidence-based brief intervention lens will expand the availability of culturally based interventions to include a grassroots intervention in the Mexican immigrant community. The juramento is organic, rooted in culture and religion, making it more likely that it will help in reducing alcohol use disorders, especially those with strong religiosity.